Rural Infrastructure Development in Uzbekistan - Farrukh, Akhrorov (Researchparks Publishing, 2023)
During the years of independence, the government of Uzbekistan has done a lot of work on the creation of industrial and agricultural infrastructure in order to revive the feelings of a dehkan of a true owner in relation to land, property and manufactured products. The priority task of the agrarian policy was that new jobs are being created due to the opening of mainly small enterprises with modern technologies, folk crafts, handicraft and handicraft workshops are developing.